Metaphysical foundations of causation: powers or laws of nature? - Sepetyi, D.; Сепетий, Дмитро Петрович (My University, 2021)
Abstract: In this article, I discuss Richard Swinburne’s case for the conception of substance causation, identified with the substances-powers-liabilities (SPL) account of causation, versus the conception of event causation, identified with alternative accounts. I specify the place of Swinburne’s argument in the debates about agent causation, and uncover reasons to be sceptical about the claims that substance causation is a genuine alternative to event causation, and that it helps to comprehend the specifics of the causation involved in free agency.
https://orcid.org/0000-0003-2110-3044
Keywords: event causation; agent causation; substance; disposition; power; power